2021
DOI: 10.1016/j.heliyon.2021.e07269
|View full text |Cite
|
Sign up to set email alerts
|

Effect of annealing temperature on structural, optical, and photocatalytic properties of titanium dioxide nanoparticles

Abstract: Titanium dioxide (TiO 2 ) nanoparticles (NPs) were produced by simple sol-gel technique and annealed for 2 h in air. The impact of annealing temperature on the physical, morphological, photocatalytic, and optical properties was studied. X-ray diffraction (XRD) measurements proved that a gradual phase change from anatase to rutile occurred with increased annealing temperature. The crystal structures of the NPs were found to change at different temperatures; anatase phase at 450 °C, mixed-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…A prepared thin film at 450 °C discloses a weak and broad hump, which possesses the mixed phase of Co 3 O 4 (2 θ = 19.03° & 36.75°) and SnO 2 (2 θ = 26.78° & 38.17°) crystal structure. In the temperature range of 600 to 1000 °C, due to the low crystalline growth, mixed phases like Co 3 O 4 , SnO 2 , Co 2 SnO 4 have been observed 60,61 and are clearly seen in Fig. 1(a).…”
Section: Resultsmentioning
confidence: 99%
“…A prepared thin film at 450 °C discloses a weak and broad hump, which possesses the mixed phase of Co 3 O 4 (2 θ = 19.03° & 36.75°) and SnO 2 (2 θ = 26.78° & 38.17°) crystal structure. In the temperature range of 600 to 1000 °C, due to the low crystalline growth, mixed phases like Co 3 O 4 , SnO 2 , Co 2 SnO 4 have been observed 60,61 and are clearly seen in Fig. 1(a).…”
Section: Resultsmentioning
confidence: 99%
“…The XRD data were recorded by scanning 2θ from 20° to 90°. The crystallite size (D) for TiO 2 and doped TiO 2 samples were calculated by using the Debye-Scherrer formula from the XRD analysis [15,18] as shown in Equation ( 1). This equation is a well-known method for calculating the crystallite size based on the line broadening for the XRD peaks at their full width at half maximum (FWHM).…”
Section: Samples Characterisationmentioning
confidence: 99%
“…Contradictory opinions on the role of oxygen vacancies in the catalytic processes have been reported [10–12] . Previous works on reference TiO 2 n‐type photocatalysts have revealed that the photocatalytic activity can be enhanced by increasing the concentration ratio of surface defects to bulk defects by annealing [13,14] or by doping [15,16] …”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Contradictory opinions on the role of oxygen vacancies in the catalytic processes have been reported. [10][11][12] Previous works on reference TiO 2 n-type photocatalysts have revealed that the photocatalytic activity can be enhanced by increasing the concentration ratio of surface defects to bulk defects by annealing [13,14] or by doping. [15,16] Likewise, choosing the right morphology plays a crucial role in structural stability and photocatalytic activity, influencing the preferential charge localization and transfer rate.…”
Section: Introductionmentioning
confidence: 99%